Determinasi Kualitas Fisik dan Kimia dedak Padi di Kota dan Kabupaten Malang Jawa Timur (Jurnal Ternak : Jurnal Ilmiah Fakultas Peternakan Universitas Islam Lamongan, 2024)
Rice bran is a by-product of milling grain into rice. Rice bran is an energy source feed ingredient that is used in both poultry and ruminant feed. The availability of rice bran in Indonesia is very abundant, but the quality varies greatly and is prone to counterfeiting. Chemical testing of rice bran quality is less economical for farmers to apply. One simple quality test to estimate the chemical quality of rice bran in the field is to use physical properties (bulk density, tapped density, true density, angel of repose). This research aims to evaluate the physical and chemical quality of rice bran in Malang City and Regency, East Java, and to create a chemical quality estimation model in the form of crude protein and crude fiber of rice bran through regression analysis and correlation of physical test results. The research results show that bulk density, tapped density, true density, and angle of repose in Malang City and Regency are very diverse. The quality of rice bran in Malang City and Regency, East Java varies greatly. Eleven sub-districts do not have quality rice bran. The physical properties of rice bran in the form of bulk density, tapped density, true density, and angel of repose are highest in Klojen District and the lowest in Pakis District. The highest crude protein content in rice bran is in Klojen District, whereas the lowest crude protein content in rice bran is in Pakis District. The correlation between crude protein and crude fiber on bulk density, tapped density, true density, and angle of repose is very close.